Transition towards digitalized communication solutions in business-critical communications - Vuorela, Vili (2020)
The industry is in a technological revolution. One portion of the revolution is upgrading existing communication systems to newer communication solutions. At the moment, business-critical communication is carried out with radiophones, where the speech is transferred to other recipients with push-to- talk functions. In industry, commonly used technology is TETRA-technology, which is about to be replaced. Companies providing communication products are developing next-generation solutions. The successor is a smartphone-based solution operating in ordinary cellular networks, which means a radiophone application. Such applications are not yet widely available on the market, and the adaptation has not been studied. It is crucial to study the topic to make the transition to alternative solutions as easy and as fast as possible for the organizations. The study presents the current state of communication solutions, on what bases the applications are built, and how people adopt new technologies. The study itself was carried out in collaboration with a partner company that provided the interviewees and a platform to be studied. The main results of the study are the features that applications require to have. With the results, organizations can implement these new applications as well as get insight into how the applications should be implemented. The main research result of the study is that the applications must be reliable, ubiquitous, and simple to use. The multimedia features that can be implemented with other smartphone features add value to the application but are not the essential features of the application.